Manajemen Investasi Wakaf Uang - Muhammad Maksum (IAIN Salatiga, 2010)
The expansion of cash waqf is constrained of the legal status still be debatable and the investment of waqf limited only on Islamic banking. MUI fatwas can be used as the basis of money in addition to the validity of the practice of cash waqf in the early Islamic period. Waqf investment money needs to be developed not only through Islamic banking as currently practiced. Cash waqf can be invested directly to the real sector, especially to finance small and medium enterprises. Islamic instruments such as Islamic bonds, stocks, mutual funds, and Islamic financial institutions such as cooperatives sharia, Islamic insurance, Islamic financing, Islamic leasing can be used as a means of investing waqf. Importantly, any type of investment must be secured to keep the cash waqf guaranteed. Keywords: cash waqf, investment, sharia principle